Consciência fonológica e aquisição da escrita: um estudo com crianças do 1° ano do ensino fundamental - Siccherino, Luciene Aparecida Felipe (2007)
The main purpose of this research is study relation between phonologic conscience and writing language acquisition in fundamental first year teaching children in two moments: in the beginning of the year and three month later. 53 children registered in a private school of Mauá city, in São Paulo State, took part in this research. Tests of individual applying were used to evaluate phonologic conscience. A dictation of collective application was applied to writing evaluation. The results proved a very significant correlation between phonologic conscience and writing skills, as much in the first application as in the second one. In the meantime, the level of phonologic skills development in the beginning on the year does not look associated with the writing skills three month later, what take us to achieve the conclusion of absence of precedence relation and an existence of loan influence between these two studied skills. Considerations about the pedagogic implications of these results are made